Mitochondrial control of innate immune responses - Chen, Shasha; Liao, Zhiyong; Xu, Pinglong (Frontiers in Immunology, 2023)
Mitochondria are versatile organelles and essential components of numerous biological processes such as energy metabolism, signal transduction, and cell fate determination. In recent years, their critical roles in innate immunity have come to the forefront, highlighting impacts on pathogenic defense, tissue homeostasis, and degenerative diseases. This review offers an in-depth and comprehensive examination of the multifaceted mechanisms underlying the interactions between mitochondria and innate immune responses. We will delve into the roles of healthy mitochondria as platforms for signalosome assembly, the release of mitochondrial components as signaling messengers, and the regulation of signaling via mitophagy, particularly to cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) signaling and inflammasomes. Furthermore, the review will explore the impacts of mitochondrial proteins and metabolites on modulating innate immune responses, the polarization of innate immune cells, and their implications on infectious and inflammatory diseases.